Tsentr dokumentatsii noveishei istorii Kirovskoi oblasti : putevoditel' = Documentation Center of the History of Kirov Region - sostaviteli M. P. Akhrameeva et al.. (Zven'ia, 1999)
Includes bibliographical references (p. 500-503).